PENGARUH MASA KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI KANTOR SATUAN POLISI PAMONG PRAJA (SATPOL-PP) KABUPATEN INDRAGIRI HULU - Windartini, Sry (JURNAL MANAJEMEN DAN BISNIS, 2018)
The purpose of this research is to examine the influence of the working life and leadership for employee performance in Satuan Polisi Pamong Praja (SATPOL-PP) Office Kabupaten Indragiri Hulu. The relevant data are taken with quantity and quality analyses. Data analyses method used are interview, validity and realibility test of multiple regression analysis, correlation coefficient, t test, and f test. The conclusion from the results above is the working life and leadership for employee performance in Satuan Polisi Pamong Praja (SATPOL-PP) Office Kabupaten Indragiri Hulu. F test show that variable of the working life and leadership have significant influence for employee performance in Satuan Polisi Pamong Praja (SATPOL-PP) Office Kabupaten Indragiri Hulu at the 5% significant level. T test show that variable of working life and leadership have significant influence for employee performance in Satuan Polisi Pamong Praja (SATPOL-PP) Office Kabupaten Indragiri Hulu at the 5% significant level. Correlation coefficient show that variable working life and leadership have significant for employee performance in Satuan Polisi Pamong Praja (SATPOL-PP) Office Kabupaten Indragiri Hulu. Working life and leadership could explain the changes in the employee performance in Satuan Polisi Pamong Praja (SATPOL-PP) Office Kabupaten Indragiri Hulu for 82.5 percent and the balance of  17.5 percent is explained by the other variables which did not included in the this research.